2017
DOI: 10.3389/fpls.2017.00866
|View full text |Cite
|
Sign up to set email alerts
|

Katanin Effects on Dynamics of Cortical Microtubules and Mitotic Arrays in Arabidopsis thaliana Revealed by Advanced Live-Cell Imaging

Abstract: Katanin is the only microtubule severing protein identified in plants so far. Previous studies have documented its role in regulating cortical microtubule organization during cell growth and morphogenesis. Although, some cell division defects are reported in KATANIN mutants, it is not clear whether or how katanin activity may affect microtubule dynamics in interphase cells, as well as the progression of mitosis and cytokinesis and the orientation of cell division plane (CDP). For this reason, we characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 71 publications
6
75
0
Order By: Relevance
“…Our model has the potential to identify the correct placement of the symmetric division plane in cells with any shape. Defects in cortical microtubule organization or other defects can lead to aberrantly shaped daughter cells (Kirik et al, 2012;Pietra et al, 2013;Hashimoto, 2015;Komis et al, 2017;Martinez et al, 2017). In mutants with aberrant cell shapes, it can be difficult to determine whether the symmetric division plane specified by the PPB follows the geometry of the cell (Pietra et al, 2013;Lipka et al, 2014;Martinez et al, 2017;Mir et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our model has the potential to identify the correct placement of the symmetric division plane in cells with any shape. Defects in cortical microtubule organization or other defects can lead to aberrantly shaped daughter cells (Kirik et al, 2012;Pietra et al, 2013;Hashimoto, 2015;Komis et al, 2017;Martinez et al, 2017). In mutants with aberrant cell shapes, it can be difficult to determine whether the symmetric division plane specified by the PPB follows the geometry of the cell (Pietra et al, 2013;Lipka et al, 2014;Martinez et al, 2017;Mir et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…5c). Severing by p60-katanin is pivotal for the organization of microtubule arrays in interphase and mitotic [10, 11, 1720] cells. However, it has been suggested that, although critical for cortical microtubule orientation in fast elongating cells, severing is not important in interphase meristematic cells, the microtubule pattern of which was described as random [21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…In the land plant Arabidopsis thaliana, the p60 subunit is encoded by a single gene called KTN1 (Burk et al, 2001;Stoppin-Mellet et al, 2002) and null mutants exhibit developmental defects that are associated with aberrant organization of interphase and mitotic microtubule arrays (Bichet et al, 2001;Burk and Ye, 2002;Boquin et al, 2003;Komis, Luptovčiak , Ovečka, et al, 2017). Live-imaging studies of the interphase cortical microtubule array revealed that KTN1 severs microtubules almost exclusively at microtubule crossover junctions and at nucleation sites to generate coaligned microtubule organization and to drive light-induced array reorientation (Wightman, Chomicki, et al, 2013;Nakamura et al, 2010;Zhang et al, 2013;Lindeboom et al, 2013;Fan et al, 2108).…”
Section: Introductionmentioning
confidence: 99%